(3GdJhbja Ydi egeGJ GdJYGQjas - (3eMeO YHO GdQDha Hf JGL GdYGQajf GHf Ydj Hf Rjf GdYGHOjf GdMOGOj Ke GdefGhj GdbGgQj, Rjf GdOjf ,J (B1031 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdgeRI haUd GdHGA GdBHGTOI GdGeJfGY hcd GHGA GeJfGY hdG YcS s
(3BNQgG (B:s
(3GdjhfSjI GUMGH jhfS Hf YHO GdQMef bGdhG Gf Gddg JYGdi Ydi GdYQT JMedI GdedGFcI JYGdi Gddg YeG jbhd GdXGdehf YdhkG cHjQkG Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdcQGSI GdChdi HNW MOjKs
(3cJHJ ai MjGI GdeDda cJHJ HYV cdeGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs